Synthesis of Carboxylated Chitosan Amide Using Some Cyclic Anhydride and Their Activities as Antifungal - Ismiyarto, Ismiyarto; Mumtazati, Qonita; Pandelaki, Elmi Christi Julia; Fachriyah, Enny; Ngadiwiyana, Ngadiwiyana; Sarjono, Purbowatiningrum Ria; Prasetya, Nor Basid Adiwibawa (Syarif Hidayatullah State Islamic University, 2023)
Chitosan is a natural polymer that has antifungal activity. It is necessary to modify chitosan into its derivatives to increase its activity. One modification of chitosan that has the potential to be developed as an antifungal is carboxylated chitosan amide because this chitosan derivative contains a carboxylic group and is more hydrophilic. This research aims to synthesize chitosan amide carboxylate using several cyclic anhydride compounds and test its antifungal activity against Aspergillus flavus. The cyclic anhydrides used in this research are maleic anhydride and phthalic anhydride. In the initial stage of chitosan amide carboxylate synthesis, reaction optimization was carried out at varying temperatures of 25, 50, and 72oC for 7 hours. Compound characterization was carried out using FTIR and UV-Vis spectrophotometry. The disc diffusion method tested the chitosan amide carboxylate product for its antifungal activity against Aspergillus flavus. The optimal MCA (Maleoyl Chitosan Amide) product is (MCA_50), synthesized at a reaction temperature of 50oC. Under these optimal reaction conditions, PCA_50 (Pthaloyl Chitosan Amide) was successfully synthesized to produce a brownish-yellow solid with a yield of 46.1% (w/w) and a degree of substitution (DS) of 41.93%. The diameter of the inhibition zone against Aspergillus flavus for PCA_50 was 30 mm at the 12th hour of observation. The product (PCA_50) has better antifungal activity than chitosan and MCA_50.